BATON-CRC: A Phase II Randomized Trial Comparing Tivozanib Plus mFOLFOX6 with Bevacizumab Plus mFOLFOX6 in Stage IV Metastatic Colorectal Cancer - Benson, Al B; Kiss, Igor; Bridgewater, John; Eskens, Ferry A L M; Sasse, Carolyn; Vossen, Sandra; Chen, Jihong; Van Sant, Chip; Ball, Howard A; Keating, Anne; Krivoshik, Andrew (Clinical cancer research, 2016)
PURPOSE: Tivozanib, a selective inhibitor of VEGFR-1, -2, and -3, plus mFOLFOX6 in an advanced gastrointestinal cancer phase Ib study had encouraging antineoplastic activity and a tolerable safety profile. This randomized, open-label, phase II trial of tivozanib/mFOLFOX6 versus bevacizumab/mFOLFOX6 in patients with previously untreated metastatic colorectal cancer (mCRC) evaluated tivozanib activity versus bevacizumab. EXPERIMENTAL DESIGN: Treatment-naïve patients received mFOLFOX6 every 2 weeks of each 28-day cycle plus either tivozanib orally 1.5 mg once daily for 21 days or bevacizumab intravenously 5 mg/kg every 2 weeks. Investigator-assessed progression-free survival (PFS) was the primary endpoint; some secondary endpoints included safety, overall survival, overall response rate (ORR), duration of response, time to treatment failure, and biomarker subgroup analyses. RESULTS: A prespecified interim futility analysis demonstrated that the futility boundary for superiority of tivozanib/mFOLFOX6 over bevacizumab/mFOLFOX6 for PFS in the intent-to-treat population was crossed; median PFS was 9.4 versus 10.7 months [HR = 1.091; confidence interval (CI), 0.693-1.718; P = 0.706]. Tivozanib/mFOLFOX6 resulted in PFS and ORR comparable with bevacizumab/mFOLFOX6; interim analyses biomarker results revealed no significant PFS association. Post hoc final analyses demonstrated a potential difference in tivozanib-specific PFS in patients with low neuropilin-1 (NRP-1), but not in patients with high NRP-1. Tivozanib/mFOLFOX6 was tolerable and adverse events were comparable with both bevacizumab/mFOLFOX6 and previous tivozanib studies. CONCLUSIONS: The efficacy of tivozanib/mFOLFOX6 was comparable with but not superior to bevacizumab/mFOLFOX6 in patients with previously untreated mCRC. Since data from the prespecified interim analysis did not demonstrate superiority, this resulted in discontinuation of the study. The safety and tolerability profile of tivozanib/mFOLFOX6 was consistent with other tivozanib trials. NRP-1 is a potential predictive biomarker for tivozanib activity, but these results require further validation. Clin Cancer Res; 22(20); 5058-67. ©2016 AACR.
Keywords: organoplatinové sloučeniny; chinoliny; Bevacizumab; Male; progrese nemoci; fenylmočovinové sloučeniny; lidé; lidé středního věku; přežití bez známek nemoci; Humans; Disease-Free Survival; Angiogenesis Inhibitors; Antineoplastic Combined Chemotherapy Protocols; Quinolines; Middle Aged; Biomarkers, Tumor; nádorové biomarkery; fluoruracil; neuropilin-1; Neuropilin-1; bevacizumab; protokoly protinádorové kombinované chemoterapie; Colorectal Neoplasms; Receptors, Vascular Endothelial Growth Factor; Fluorouracil; Organoplatinum Compounds; mužské pohlaví; inhibitory angiogeneze; kolorektální nádory; Phenylurea Compounds; Disease Progression; receptory vaskulárního endoteliálního růstového faktoru; ženské pohlaví; Female; Leucovorin; leukovorin